2005
DOI: 10.1080/014850190518125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Abnormal Sperm Chromatin Structural Assay (Scsa) on Pregnancy Outcome Following (Ivf) With Icsi in Previous Ivf Failures

Abstract: A high DNA fragmentation index (DFI) when performing the sperm chromatin structural (SCSA) assay was claimed to be so specific for male subfertility that even IVF and ICSI did not result in live pregnancies. The present study was designed to corroborate or refute these findings. The SCSA test was performed on the male partner from couples failing to have a successful pregnancy despite at least 2 previous IVF attempts. In contrast to the aforementioned studies, ongoing pregnancies were found despite working wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 19 publications
9
45
0
2
Order By: Relevance
“…Several studies have failed to confirm these earlier findings by demonstrating no significant differences in pregnancy rates following IVF or ICSI between patients with high and low levels of sperm DNA damage [13,16,17,46,63,108,131]. Successful pregnancies have also been obtained using IVF or ICSI cycles despite high levels of sperm chromatin damage (DFI > 27%) [16,17,21,46]. A recent study found no significant differences in IVF and ICSI pregnancy outcomes between low and high DFI groups.…”
Section: In Vitro Fertilizationmentioning
confidence: 54%
“…Several studies have failed to confirm these earlier findings by demonstrating no significant differences in pregnancy rates following IVF or ICSI between patients with high and low levels of sperm DNA damage [13,16,17,46,63,108,131]. Successful pregnancies have also been obtained using IVF or ICSI cycles despite high levels of sperm chromatin damage (DFI > 27%) [16,17,21,46]. A recent study found no significant differences in IVF and ICSI pregnancy outcomes between low and high DFI groups.…”
Section: In Vitro Fertilizationmentioning
confidence: 54%
“…As with IVF studies, these ICSI studies are quite heterogeneous in terms of design, inclusion/exclusion criteria, and the sperm DNA damage test employed. In keeping with a recent analysis [Collins et al 2008], the results of this updated meta-analysis on ICSI studies indicate that sperm DNA damage is not related to ICSI pregnancy rates (combined OR of 1.15, 95% 0.90, 1.55, p = 0.65) [Benchaib et al 2007;Boe-Hansen et al 2006;Borini et al 2006;Bungum et al 2007;Check et al 2005;Gandini et al 2004;Hammadeh et al 1996;Henkel et al 2003;Host et al 2000;Huang et al 2005;Lin et al 2008;Micinski et al 2009;Tarozzi et al 2009;Zini et al 2005]. The characteristics of the 14 ICSI studies that could be evaluated are shown in Tables 4 and 5.…”
Section: In Vitro Fertilization With Intracytoplasmic Sperm Injectionmentioning
confidence: 81%
“…Recent study by Venkatesh et al, 2009 andLewis et al, 2010 [12, 13] showed that there is no correlation between oxidative stress (OS) or DNA damage with SSP. So there is a need to have specific diagnostic tests for the assessment of OS and DNA damage Studies both, in vitro and in vivo have shown that there is a negative correlation between sperm DNA integrity and fertility [14][15][16][17][18][19][20]. DNA damage is associated with poor embryo development, decreased implantation, and poor pregnancy outcome [21].…”
Section: Introductionmentioning
confidence: 99%